2022
DOI: 10.17509/jaset.v14i1.45978
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Of Monopoly Accounting Game Media In Increasing Motivation And Learning Outcomes

Abstract: Abstrak Tujuan Utama – Penelitian inimemiliki tujuan untuk mengetahui efektivitas penggunaan media monopoly accounting game dalam proses pembelajaran untuk meningkatkan motivasi dan hasil belajar mahasiswa dalam mata kuliah Pengantar Akuntansi.Metode – Metode eksperimen dengan desain Nonequivalent Control Group Design merupakan metode penelitian yang digunakan dalam penelitian. Dalam penelitian ini, siswa dibagi menjadi dua kelompok yang berbeda: kelompok kontrol dan kelompok eksperimen.Temuan Utama – Hasil pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Research (Y. P. Sari et al, 2020) states that there is an effect of using monopoly learning media on student learning outcomes, as shown by the increase in pretest-posttest results in the experimental class. According to (Buchory et al, 2022), the use of game media in learning, such as monopoly media, significantly improved students' problem-solving skills and concept understanding in accounting subjects. Research (GUMILANG, 2019) showed that Monopoly media increased students' interest in learning accounting, which in turn had a positive impact on their learning outcomes.…”
mentioning
confidence: 99%
“…Research (Y. P. Sari et al, 2020) states that there is an effect of using monopoly learning media on student learning outcomes, as shown by the increase in pretest-posttest results in the experimental class. According to (Buchory et al, 2022), the use of game media in learning, such as monopoly media, significantly improved students' problem-solving skills and concept understanding in accounting subjects. Research (GUMILANG, 2019) showed that Monopoly media increased students' interest in learning accounting, which in turn had a positive impact on their learning outcomes.…”
mentioning
confidence: 99%